Discrete Element Simulation of the Relationship between Composition, ITZ Property, and Tensile Behavior of Eco-Friendly UHPC Matrix - Zhou, Xiang; Shi, Ye; Hu, Qingchun; Zhang, Shen; Zhang, Xihong; Meng, Lingzhen (2023)
To combat global warming, the development of eco-friendly ultra-high performance concrete (UHPC) has become one of the current research hotspots. Understanding the relationship between composition and performance of eco-friendly UHPC from a meso-mechanical point will be of great significance in proposing a more scientific and effective mix design theory. In this paper, the 3D discrete element model (DEM) of an eco-friendly UHPC matrix was constructed. The mechanism of the effect of the interface transition zone (ITZ) properties on the tensile behavior of an eco-friendly UHPC matrix was studied. The relationship between composition, ITZ property, and tensile behavior of eco-friendly UHPC matrix was analyzed. The results show that ITZ strength influences the tensile strength and cracking behavior of eco-friendly UHPC matrix. The effect of ITZ on the tensile properties of eco-friendly UHPC matrix is more significant than that of normal concrete. The tensile strength of UHPC will be increased by 48% when the ITZ property is changed from normal condition to perfect. Improving the reactivity of the binder system of UHPC will improve the performance of ITZ. The cement content in UHPC was reduced from 80% to 35%, and the σITZ/σPaste was reduced from 0.7 to 0.32. Both nanomaterials and chemical activators can promote the hydration reaction of the binder material, which in turn leads to better ITZ strength and tensile properties for an eco-friendly UHPC matrix.